2022
DOI: 10.3390/su142315824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organizational Culture on Academics’ Readiness and Behavioral Intention to Implement eLearning Changes in Kuwaiti Universities during COVID-19

Abstract: A comprehensive review of the literature indicates that there is a lack of research on the influence of all the organizational culture (OC) types on academics’ readiness and behavioral intention to implement eLearning changes in higher education institutions (HEIs). To address this gap, this study empirically investigates the impact of OC on academics’ readiness and behavioral intention to implement eLearning changes within HEIs in Kuwait during the COVID-19 pandemic. A 218 self-administered survey was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…The results showed that lecturers' expectations, perceived ease of use, and preparedness had a direct influence on satisfaction. Culture was also found to correlate strongly with lecturer's satisfaction with e-learning [33]. Perceived enjoyment was also reported to have a significant influence on satisfaction [32].…”
Section: Factors That Influence Instructors' Satisfaction With E-lear...mentioning
confidence: 86%
“…The results showed that lecturers' expectations, perceived ease of use, and preparedness had a direct influence on satisfaction. Culture was also found to correlate strongly with lecturer's satisfaction with e-learning [33]. Perceived enjoyment was also reported to have a significant influence on satisfaction [32].…”
Section: Factors That Influence Instructors' Satisfaction With E-lear...mentioning
confidence: 86%
“…Zhen et al (2021) also assert that digital capabilities, organizational culture, and innovation are judged by organizational preparedness and that digital capabilities impact organizational readiness. In higher education, both Al-Shamali et al (2022) and Haffar et al (2023) show that organizational culture positively correlated with readiness for change. Accordingly, the subsequent hypothesis is produced:…”
Section: Digital Capabilities and Organizational Readinessmentioning
confidence: 99%
“…Studies examining the influence of top management on organizational culture and behavioural intentions have shown a strong relationship between organizational culture and behavioural intentions; organizational culture is also a strong predictor (Hu et al, 2012). Al-Shamali et al (2022), who aimed to determine the types of organizational culture in higher education institutions and their effects on academics' readiness to implement e-learning changes and their behavioural intentions, found that organizational culture positively affects academics' behavioural intentions. Hallikainen et al (2017) found that the impact of organizational culture on the behavioural intentions of individuals to use digital services in the purchasing process of B2B customers, together with their readiness for technology, organizational culture was found to be a strong predictor of individuals' behavioural intentions.…”
Section: Green Culture and Green Behavioural Intentionsmentioning
confidence: 99%